PENGETAHUAN LOKAL MASYARAKAT SAMIN TENTANG KEANEKARAGAMAN TUMBUHAN DAN PENGELOLAANYA - Jumari .; Dede Setiadi; Y. Purwanto; Edi Gurhardja (Department of Forest Resources Conservation and Ecotourism - IPB University, 2012)
The aims of the study is to reveal of local knowledge the Samin society about the diversity of plant species is usefulness, the utilization category, the potential use, value of cultural and concept of traditional conservation. The location of observation are 7 villages: Larikrejo and Kaliyoso (Kudus); Bombong and Ngawen (Pati); Klopoduwur and Tambak (Blora); Margomulyo (Bojonegoro). Data collection using survey and open ended interview techniques. Useful plant inventory carrying more than 235 species of plants; as 118 species of food; ingredient in traditional medicines 74 species: 16 species of building materials; equipment and craft materials 15 species: 16 species of firewood; 27 species of animal feed; fiber materials and rope three species, two species of fish poisons; pest control materials 16 species and ornamental plants 25 species. The most of useful plant species (80% ) are cultivated plant and 25% intensity value utilization of this species is high. The results of calculation of the Indeks of Cultural Signification found the species that have important value is the highest Oryza sativa L. and the second is Tectona grandis L.f. Keyword: local knowledge, plant diversity, plant conservation, Indeks of Cultural Signification, Samin Society